2005
DOI: 10.1109/tpc.2004.843299
|View full text |Cite
|
Sign up to set email alerts
|

Team Size and Technology Fit: Participation, Awareness,and Rapport in Distributed Teams

Abstract: Abstract-In this paper we investigate the effects that team size has on geographically distributed team behavior and technology choice. We report results from a survey of distributed team members conducted within a large, multi-national technology manufacturing organization. Responses indicate that members of smaller teams participated more actively on their team, were more committed to their team, were more aware of the goals of the team, had greater awareness of other team members, and were in teams with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 22 publications
0
45
0
1
Order By: Relevance
“…non-mediated) in decentralized companies confirms those observations made in mediated groups. For example, on examining the influence of the participation of employees depending on the size of project teams, Bradner et al observed that participation is higher in small groups compared to large ones [11]. The group coherence that is obtained by a strong initial and consensual motivation, by the definition of clear shared goals or by a mediator who drives the group, contribute to facilitating the process of individual decision, which feeds back on collective relation and maintains the involvement of the group members (see also section 4.2).…”
Section: Examples Of Online Forums: Discussion Topic Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…non-mediated) in decentralized companies confirms those observations made in mediated groups. For example, on examining the influence of the participation of employees depending on the size of project teams, Bradner et al observed that participation is higher in small groups compared to large ones [11]. The group coherence that is obtained by a strong initial and consensual motivation, by the definition of clear shared goals or by a mediator who drives the group, contribute to facilitating the process of individual decision, which feeds back on collective relation and maintains the involvement of the group members (see also section 4.2).…”
Section: Examples Of Online Forums: Discussion Topic Performancesmentioning
confidence: 99%
“…Various authors have studied this issue and have given apparently contradictory answers. Some studies in the context of collaborative work report that an increase of group size tends to reduce individual participation [11,22,23]. In a more detailed way, Avouris et al remark that larger groups produce better results and generate greater activity, but that this activity is less homogeneously distributed between different members of the group [24].…”
Section: Relationship Between Individual Expressivity Activity and Tmentioning
confidence: 99%
“…In order for teams to be effective, many researchers recommend that they initially meet face to face (e.g., Hertel et al, 2005;Powell et al, 2004). However, a recent study of open-source software development teams found that even when virtual communication media predominated early project phases, the teams were still effective (Bradner et al, 2005).…”
Section: Media and Team Performancementioning
confidence: 98%
“…The negative impacts occur when interpersonal interactions facilitated by rich media distract team members (Yoo and Alavi, 2001). Further, rich media can reduce task participation, while lean media may direct the members' attention to solving the task (Phillips and Santoro, 1989 (Bradner et al, 2005). Additionally, smaller teams are more likely than larger teams to choose media supporting synchronous communication (Bradner et al, 2005).…”
Section: Media and Team Performancementioning
confidence: 99%
“…co-located members' collaboration at this site should become stronger because they perceive themselves to be the primary link that holds all subgroups together 3 .…”
Section: Literature Reviewmentioning
confidence: 99%